Das Sein der Dauer - Speer, Andreas; Wirmer, David (De Gruyter, 2010)
This volume is based on the 35th Cologne Medieval Studies Conference on the Duration of Being
Volume based on the 35th Cologne Medieval Studies Conference on "Das Sein der Dauer. - Includes bibliographical references and indexes. - Chiefly German, 5 articles in English, 1 article in French. - Description based on print version record
Includes bibliographical references and indexes
Chiefly German, 5 articles in English, 1 article in French
Description based on print version record
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002
Keywords: Electronic books -- Electronic books -- Conference proceedings -- History; Konferenzschrift -- 2006 -- Köln; Begriff; Zeit; Mediävistik